Infinitely many solutions for the p-fractional Kirchhoff equations with electromagnetic fields and critical nonlinearity - Liang, Sihua; Zhang, Jihui (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, we consider the fractional Kirchhoff equations with electromagnetic fields and critical nonlinearity. By means of the concentration-compactness principle in fractional Sobolev space and the Kajikiya's new version of the symmetric mountain pass lemma, we obtain the existence of infinitely many solutions, which tend to zero for suitable positive parameters.
Keywords: fractional Kirchhoff equations; fractional magnetic operator; critical nonlinearity; variational methods